Analysis of Indonesia International Trade Policy on Domestic Component Level Policies in The Import Licensing of Iphone 16 in Indonesia - Muhammad Saeful Bahri; Rizal Budi Santoso (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study analyzes Indonesia’s international trade policy through the implementation of the Domestic Component Level (Tingkat Komponen Dalam Negeri/TKDN) requirement in the import licensing of the iPhone 16. The TKDN policy represents a form of protectionism aimed at strengthening domestic industries, reducing dependence on imported products, and encouraging foreign investment to contribute to local value creation. However, the enforcement of this policy has generated significant challenges, particularly for multinational corporations such as Apple, as reflected in the delay of iPhone 16 distribution in Indonesia in October 2024 due to non-compliance with TKDN standards. This research employs a qualitative descriptive approach using secondary data, including government regulations, policy documents, official reports, and relevant literature, supported by institutional perspectives from the Ministry of Industry and regional trade authorities. The analysis focuses on regulatory frameworks, implementation mechanisms, and the economic implications of TKDN enforcement in the smartphone sector. The findings indicate that while the TKDN policy has contributed to promoting local production, technology transfer, and workforce involvement, it also poses administrative, regulatory, and market challenges that may affect investment attractiveness and supply chain efficiency. The study highlights the need for regulatory refinement, improved certification processes, and enhanced policy coordination to ensure that TKDN effectively balances domestic industrial protection with openness to international trade and innovation.